Case report: Physiological changes due to a rapid ascent from 55 metres underwater. (February 2021) - Homsy, Michele; Bounds, Catherine; Glover, Mark; Castledine, Benjamin; Martindale, Timothy
We present the case of a diver who experienced an uncontrolled ascent from 55 m and presented with a severe decompression illness. She was clinically shocked and in multi organ failure due to massive fluid shifts. She demonstrated bilateral lower limb loss of power and sensation and required multiple hyperbaric therapy sessions. With joint critical care, hyperbaric and physical therapy involvement, she was discharged some five weeks after her presentation with an independent level of function.